Reevaluation of postoperative radiation dose in the management of human papillomavirus–positive oropharyngeal cancer. Issue 11 (6th May 2016) - Chin, Re‐I; Spencer, Christopher R.; DeWees, Todd; Hwang, Michael Y.; Patel, Pranav; Sinha, Parul; Gay, Hiram A.; Haughey, Bruce H.; Nussenbaum, Brian; Adkins, Douglas R.; Lewis, James S.; Thorstad, Wade L.
Abstract: Background: The purpose of this study was to compare outcomes of patients with p16‐positive oropharyngeal squamous cell carcinoma (SCC) treated with postoperative intensity‐modulated radiotherapy (IMRT) before and after an institutional dose reduction policy effective on February 2009. Methods: Between 1998 and 2013, 175 consecutive patients with p16‐positive oropharyngeal SCC with extracapsular extension (ECE) and/or close or positive margins were treated postoperatively to 66 Gy ( n = 109) or 60 Gy ( n = 66) in 2 Gy/fx. Results: Between the 66 and 60 Gy groups, there was no difference in tumor classification (pT4 vs pT1–T3; p = .181) and nodal classification (pN2c–N3 vs pN0–N2b; p = .704), and American Joint Committee on Cancer (AJCC) group stage (IV vs I–III; p = .473). Median follow‐up was 5.9 years overall (66 Gy: 7.4 years; 60 Gy: 4.0 years). There was no difference in locoregional recurrence‐free survival (2‐year: 98.1% vs 98.5%; p = .421). Conclusion: This study suggests that treating p16‐positive oropharyngeal SCC with ECE and/or close or positive margins with postoperative IMRT to 60 Gy may not compromise locoregional recurrence‐free survival compared to 66 Gy. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016